2022
DOI: 10.1111/jcmm.17206
|View full text |Cite
|
Sign up to set email alerts
|

CTNNAL1 participates in the regulation of mucus overproduction in HDM‐induced asthma mouse model through the YAP‐ROCK2 pathway

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…The respiratory virus infection further exacerbates the asthmatic condition, resulting in hypersecretion of airway mucus, obstructing the airway, and increasing airway resistance. Our simultaneous assessment of inflammatory factors and airway resistance in lung tissue and alveolar lavage fluid showed that respiratory viral infection also exacerbated lung inflammation and increased airway resistance in asthmatic mice by a mechanism that, in addition to being associated with the YAP/FOXM1 pathway, YAP can also exacerbate lung tissue by regulating other pathways, such as NF-κB [44,45] and YAP/ROCK2 [46] inflammatory response. Lung inflammation, goblet cell hyperplasia, and mucus hypersecretion induce asthma attacks.…”
Section: Discussionmentioning
confidence: 88%
“…The respiratory virus infection further exacerbates the asthmatic condition, resulting in hypersecretion of airway mucus, obstructing the airway, and increasing airway resistance. Our simultaneous assessment of inflammatory factors and airway resistance in lung tissue and alveolar lavage fluid showed that respiratory viral infection also exacerbated lung inflammation and increased airway resistance in asthmatic mice by a mechanism that, in addition to being associated with the YAP/FOXM1 pathway, YAP can also exacerbate lung tissue by regulating other pathways, such as NF-κB [44,45] and YAP/ROCK2 [46] inflammatory response. Lung inflammation, goblet cell hyperplasia, and mucus hypersecretion induce asthma attacks.…”
Section: Discussionmentioning
confidence: 88%
“…CTNNAL1 was found to be ubiquitously expressed in many tissues, including skeletal muscle, the pancreas, and the heart 31 . By comparing psoriasis patients who did not have psoriatic arthritis and patients with psoriatic arthritis, Patrick MT et al identi ed signi cant loci overlapping the regulatory elements that encompass genes that are differentially expressed in differentiated osteoblasts, including genes that participate in Wnt signaling, such as RUNX1, FUT8, and CTNNAL1 32 .…”
Section: Discussionmentioning
confidence: 99%
“…MUC5AC and mucin5B (MUC5B) are integral components of airway mucus [18] . In our previous study, we demonstrated that CTNNAL1 deficiency results in an increase in MUC5AC secretion but does not influence MUC5B expression [11] . CFTR is an apical membrane chloride channel critical to the regulation of fluid, chloride, and bicarbonate transport in epithelial and other cell types [19] .…”
Section: Introductionmentioning
confidence: 89%
“…There is a negative correlation between the reduction in CTNNAL1 expression and airway hyperresponsiveness [10] . CTNNAL1 deficiency enhances lung inflammation and mucus hypersecretion through activation of the YAP-ROCK2 signaling pathway [11] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation